Pediatric ABO‐incompatible kidney transplantation: Evolving with the advancing apheresis technology: A single‐center experience. (30th January 2018) - Sethi, Sidharth Kumar; Bansal, Shyam Bihari; Wadhwani, Nikita; Tiwari, Aseem; Arora, Dinesh; Sharma, Reetesh; Nandwani, Ashish; Yadav, Dinesh Kumar; Mahapatra, Amit Kumar; Jain, Manish; Jha, Pranaw; Ghosh, Prasun; et al.
Abstract: Recent literature has endorsed favorable outcomes following ABOi kidney transplantation in pediatric population. Nevertheless, reluctance to pursue an ABOi still remains pervasive. This could be ascribed to various legitimate reasons, namely less extensive pediatric ABOi data, technical difficulties encountered during PP, cost restraints, and concerns regarding higher rates of antibody‐mediated rejection, infectious complications, and post‐transplant lymphoproliferative disorder as compared to adults. However, given the similar excellent outcomes of both ABOi and ABOc kidney transplantation, clinicians should consider this option sooner if a compatible donor or swap is not available. Here, we describe the outcomes of three pediatric ABOi performed at our institute in India (from 2014 till now), wherein distinct apheresis modalities had been employed in each desensitization protocol, and our techniques evolved with advancing science in apheresis. This case series includes India's first published pediatric ABO‐incompatible transplant (Case 2) and the youngest child to undergo ABO‐incompatible renal transplant in SAARC nations (Case 3).